Characteristics of patients with diagnosis of maturity-onset diabetes of the young, according to the Russian diabetes registry - N. V. Rusyaeva; I. V. Kononenko; O. K. Vikulova; M. A. Isakov; M. V. Shestakova; N. G. Mokrysheva (Сахарный диабет)
BACKGROUND: Molecular genetic testing (MGT) is increasingly accessible, improving diagnosis of monogenic diabetes (DM), particularly maturity-onset diabetes of the young (MODY). While most MODY research focuses on pediatric populations, diagnosis is possible after age 18. The Federal Diabetes Registry (FDR) offers unique insights into real-world management of MODY patients.AIM: To analyze the clinical features of DM onset, carbohydrate metabolism, complications, and hypoglycemic therapy (HT) in patients with the main types of MODY based on the FDR data.MATERIALS AND METHODS: A cross-sectional analysis of the FDR was conducted. All patients with registered MODY diagnoses (MODY-1, MODY-2, MODY-3, or other) as of June 1, 2023, were included. The specified MODY type was considered indicative of prior MGT. Direct MGT results are not recorded in the FDR.RESULTS: The study included 640 patients. MODY2 was the most prevalent type (69.4%), followed by MODY1 (18.2%) and MODY3 (12.4%). The median age of DM diagnosis was 19 years for MODY1, 10 years for MODY2, and 14 years for MODY3. The majority of patients (71.4%) were diagnosed with MODY before the age of 18 years.While 61% of MODY2 patients received monotherapy with diet, others received various ADT. Sulfonylureas were commonly prescribed for MODY3 patients (45.8%), and for a smaller portion of MODY1 patients (14.1%). Insulin therapy was more frequent in MODY1 and 3 (35.9% and 31.2%, respectively). The target glycated hemoglobin level was achieved in 82% of MODY2 patients and in 50.7% and 52.9% of MODY1 and 3 patients, respectively.Diabetic complications were observed in 6.04% of MODY2 patients, 23.0% of MODY1 patients, and 22.0% of MODY3 patients. Specific complications included diabetic retinopathy (5.75%, 1.21%, and 3.39% in MODY1, MODY2, and MODY3, respectively), diabetic nephropathy (10.3%, 2.11%, and 11.9%), and diabetic polyneuropathy (14.9%, 4.53%, and 15.3%).CONCLUSION: The FDR analysis revealed real-world practice patterns in MODY management, highlighting a lack of standardized treatment approaches and potentially unnecessary insulin use. These findings, coupled with an expected rise in MODY diagnoses, underscore the need for clinical guidelines for this population.